Desarrollo conceptual de los factores críticos de éxito en la adquisición y fusión de empresas: contexto para un estudio de organizaciones mexicanas - Rodríguez Miechielsen, Alejandro Javier; Alarcón Martinez, Gustavo Juan; Mendoza Gómez, Joel (Facultad de Contaduría Pública y Administración U.A.N.L., 2013)
Abstract: This paper presents a conceptual development on the variables that make up the processes of acquisition and merger holding companies in pursuit of greater strategic value creation. From research questions, is reviewed in detail each of the variables of these processes, in this manner, it is possible to raise further study to identify the relative importance of each of these variables. We propose a graphical model that integrates the conceptual development of this work.